Human Immunodeficiency Virus Preexposure Prophylaxis Knowledge, Attitudes and Perceptions of Sexual Health Risk in an Age of Sexually Transmitted Infection Antimicrobial Resistance. Issue 9 (September 2021) - Lorenc, Ava; Nicholls, Jane; Kesten, Joanna May; Macgregor, Louis; Speare, Nathan; Harryman, Lindsey; Turner, Katy M.E.; Horner, Patrick; Horwood, Jeremy
Abstract : Background: Human immunodeficiency virus (HIV) preexposure prophylaxis (PrEP) has helped reduce new HIV infections. However, bacterial sexually transmitted infections (STIs) have increased among PrEP users. We examined PrEP knowledge, access, and risk perceptions in an age of antimicrobial resistance (AMR). Methods: An online anonymous survey was distributed to all cisgender men/transpersons who have sex with men attending a sexual health clinic in Bristol, United Kingdom (October 2018 to November 2019). Interviews with a sample identified at increased risk of HIV were analyzed thematically and integrated with survey data. Results: Five hundred and seventy-eight (95%) of 617 cisgender men/transpersons who have sex with men survey respondents were HIV-negative/unknown, of these, 202 (34.9%) had ever used PrEP. Interviewees (n = 24) reported widespread awareness of and enthusiasm for PrEP. Among nonusers, 39% (146/376) were unaware how to access PrEP, and 27% (103/376) could not access PrEP through the national "impact" trial of whom 79% (81/103) were eligible. The PrEP was described as "life-changing, " but expense was the main barrier to use. Sixty-two percent (358/578) of HIV-negative/unknown respondents on PrEP were more likely to have condomless anal intercourse with someone they thought was HIV-negative. Interviewees used PrEP with other risk-reduction strategies. Sexually transmitted infections were seen as "curable" and AMR rarely influenced risk perception or sexual decision making. Conclusions: The PrEP awareness was high, but purchase cost limited access. PrEP may increase condomless anal intercourse, but interviewees used PrEP as one of many risk-reduction tools. Reduced fear of HIV transmission and testing was highly valued. Sexually transmitted infection AMR was not seen as an immediate threat and did not influence risk perception or sexual decision making. Abstract : A mixed methods study of cisgender men/transpersons who have sex with men sexual health clinic attendees found that preexposure prophylaxis reduced anxiety and may increase likelihood of condomless anal intercourse, but risk of sexually transmitted infection antimicrobial resistance was not seen as an immediate threat.Supplemental digital content is available in the text.